1998
DOI: 10.1524/zkri.1998.213.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal Mössbauer and neutron powder diffraction measurements on the synthetic clinopyroxene Li-acmite LiFeSi2O6

Abstract: Mössbauer experiments on a Li-acmite single crystal section with the crystallographic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…5,17 However it turns out for the moment that most of the pyroxenes exhibit a simple magnetic structure commensurate with the lattice with k = 0. 7,11,12,14,15 Nevertheless, several of those reported magnetic structures are compatible with a linear magnetoelectric effect. 7,14,15 In this contribution, we continue our investigation of the crystal and magnetic structures of the pyroxene family with its ferromagnetic member: NaCrGe 2 O 6 .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…5,17 However it turns out for the moment that most of the pyroxenes exhibit a simple magnetic structure commensurate with the lattice with k = 0. 7,11,12,14,15 Nevertheless, several of those reported magnetic structures are compatible with a linear magnetoelectric effect. 7,14,15 In this contribution, we continue our investigation of the crystal and magnetic structures of the pyroxene family with its ferromagnetic member: NaCrGe 2 O 6 .…”
Section: Introductionmentioning
confidence: 89%
“…7 While these pyroxenes have been the subject of various studies, [5][6][7][8][9][10][11][12] the complete magnetic structures are known only for few members of this class. 7,[11][12][13][14][15] We have started recently to investigate the magnetic structure of several pyroxene materials. [14][15][16] The investigation of this magnetically frustrated family by neutron diffraction is of prime importance in the interpretation and/or prediction of their multiferroic/ magnetoelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…This especially holds true for the Li clinopyroxenes, which thus qualifies them as a favorite object for crystal-chemical investigations in the P-T-X space. The most common structural phase transition is the P2 1 /c ⇔ high-temperature HT-C2/c phase transition, which occurs at 229 K in LiFeSi 2 O 6 as described in detail by Lottermoser et al (1998), Redhammer et al (2001), and Redhammer and Roth (2004b).…”
Section: Introductionmentioning
confidence: 99%
“…23 Jodlauk et al have reported that they observe a magnetically induced electrical polarization not only in LiCrSi 2 O 6 but also in LiFeSi 2 O 6 . Several studies using powder and single crystal report a magnetic structure described by the magnetic space group P2 1 / c. 11,12 This magnetic symmetry forbids any linear magnetoelectric effect since it contains the inversion symmetry. 23 Consequently there is a discrepancy between the reported induced electrical polarization by Jodlauk et al and the reported magnetic symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…7 While these pyroxenes have been the subject of various studies, [5][6][7][8][9][10][11][12] the complete magnetic structures are known only for few members of this class. 7,[11][12][13] In order to understand and interpret properly the interplay between the dielectric and magnetic properties of this new multiferroic family, the determination of the magnetic structure of their members is necessary. Jodlauk et al 5 suggested that several members of the pyroxene family among which LiCrSi 2 O 6 exhibit an incommensurate magnetic structure.…”
Section: Introductionmentioning
confidence: 99%